Gender differential in inclination to donate brain for research among Nigerians: the IBADAN Brain Bank Project (2019)
Background: Laboratory-based studies of neurological disease patterns and mechanisms are sparse in sub-Saharan Africa. However, availability of human brain tissue resource depends on willingness towards brain donation. This study evaluated the level of willingness among outpatient clinic attendees in a Nigerian teaching hospital. Methods: Under the auspices of the IBADAN Brain Bank Project, a 43—itemsemi-structured interviewer—administered questionnaire was designed to evaluate knowledge, attitude, and beliefs of individuals attending Neurology, Psychiatry and Geriatrics Outpatient clinics regarding willingness to donate brain for research. Association between participants characteristics and willingness towards brain donation was investigated using logistic regression models. Analysis was conducted using Stata SE version 12.0. Results: A total of 412 participants were interviewed. Their mean age was 46.3 (16.1) years. 229 (55.6%) were females and 92.5% had at least 6 years of formal education. Overall, 109 (26.7%) were willing to donate brains for research. In analyses adjusting for educational status, religion, ethnicity, marital status and family setting, male sex showed independent association with willingness towards brain donation OR (95% CI) 1.7 (1.08–2.69), p = 0.023. Participants suggested public engagement and education through mass media (including social media) and involvement of religious and community leaders as important interventions to improve awareness and willingness towards brain donation. Conclusion: The survey revealed low willingness among outpatient clinic attendees to donate brain for research, although men were more inclined to donate. It is imperative to institute public engagement and educational interventions in order to improve consent for brain donation for research.